High‐resolution scanning transmission soft X‐ray microscopy for rapid probing of nanoparticle distribution and sufferance features in exposed cells1. (6th March 2015) - Kourousias, G.; Pascolo, L.; Marmorato, P.; Ponti, J.; Ceccone, G.; Kiskinova, M.; Gianoncelli, A.
<x xml:space="preserve">Abstract</x> Refraction and absorption properties of soft X‐rays provide distinct advantages for 'fast' imaging of matter consisting of light elements, as biological samples, with sensitivity better than conventional light microscopy. This is very attractive for nanotoxicology, in particular for rapid screening of nanoparticle distribution and their effects on exposed cells at submicrometer length scales. In this paper, we report on the first trials demonstrating the potential of scanning transmission X‐ray microscopy to monitor morphological and chemical changes induced in Balb 3T3 mouse fibroblast cells exposed to CoFe2O4 nanoparticles. This research uses the complementary imaging methods of an advanced synchrotron soft X‐ray microscopy instrument implementing a novel approach based on high‐resolution absorption and phase contrast imaging for the identification of important cellular changes induced by the presence of nanoparticles. Copyright © 2015 John Wiley & Sons, Ltd.